Bentuk Penyajian Balatindak dalam Prosesi Pakanggi Umat di Kecamatan Bangkurung Kabupaten Banggai Laut - Wida H. Saisali; Nurlia Djafar; Riana Diah Sitharesmi (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Balatindak is a traditional art that has existed since the time of the Banggai Kingdom. In its development, Balatindak presented in the regions, and each region has its own characteristics in its performance. In Banggai Laut Regency, Bangkurung District, Balatindak is performed upon the arrival of visiting distinguished guests, and on Eid al-Fitr. In Lantibung village, Balatindak is not only entertainment but also as part of the pakanggi umat ceremony carried out by the community. This study aims to describe the form of Balatindak presentation in the process of implementing pakanggi umat. This study uses a descriptive qualitative research method. In collecting data, researchers conducted interviews, and observations of the implementation of pakanggi umat, as well as documenting it in the form of photos and videos. The results of the study found that Balatindak was performed four during the pakanggi umat. The first was at the beginning of the procession performed by two men (talapu), then in the middle was presented by several male and female talapu. The costumes worn by male talakus are daily clothes consisting of long or short-sleeved shirts, black trousers, and white headbands. Meanwhile, female talapu wear long-sleeved shirts, sarongs, scarves, and white head coverings. The Balatindak is unique with movements dominated by rapid foot stomping, and both arms play props depicting machetes and shields. Balatindak is accompanied by batong music. The venue is the Bangkurung traditional house called Kusali. The Balatindak performed in this tradition classified as a ritual performing art.